The Relations between Students' Intercultural Communication Competencies and Employability - Tímea Lázár; János Farkas; Zita Hajdú; Ildikó Tar; Mária Czellér; Marcella D'Arrigo (Debrecen University Press, 2023)
In today's globalised world, businesses operate on an international level. Most business and economics graduates will interact with colleagues, clients, and partners from diverse cultural backgrounds. Intercultural competencies are essential for their success and effective collaboration in the labour market. A special questionnaire was compiled to investigate students' intercultural competencies. Based on the statements and responses of the questionnaire, the examination aimed to establish the principal components of the intercultural communication competencies of the students of a Hungarian university. In the next phase of the research, the principal components served to create student clusters which were analysed from a labour market point of view, focusing on advantages and disadvantages. The crucial question was: which cluster is in demand the most in the labour market? By utilizing a principal component analysis, the dataset was reduced to three key components. Subsequently, to classify the students into groups, a multivariate statistical procedure, i.e., cluster analysis, was used to reveal the structures by clearly considering the similarities of a relatively heterogeneous population and to create a relatively homogeneous subset. The study revealed five distinct student clusters, each with varying advantages and disadvantages for employers. In this context, the Interculturally Active and Open with Good Language Skills cluster proved to be the most competent, with the least ideal collection indisputably being the Interculturally Reluctant in Cooperating cluster. The research underscores the importance of intercultural communication competencies for employees and enriches our understanding of the dynamics between intercultural communication competencies and workforce readiness. Developing these competencies in foreign language classes will significantly facilitate our students' employment.